The Influence of Leadership, Motivation and Work Discipline on Employee Performance at PT Panjiwira Surya Mandiri Medan - Ferry Ferry; Livea Livea; Hendry Hendry (Jurnal Mantik, 2020)
This research was conducted at PT Panjiwira Surya Mandiri Medan. The purpose of this study was to determine and analyze the influence of leadership, motivation and work discipline on employee performance at PT Panjiwira Surya Mandiri Medan.This research approach is based on a quantitative approach. The population in this study amounted to 82 employees and the number of samples in the study were 82 employees. The sampling technique used was census sampling. The test uses a linear regression analysis. The conclusion in this study is that Leadership, Motivation and Work Discipline have a positive and significant effect on Employee Performance at PT Panjiwira Surya Mandiri Medan.